High‐Temperature Neutron Diffraction, Raman Spectroscopy, and First‐Principles Calculations of Ti3SnC2 and Ti2SnC. Issue 7 (26th March 2016) - Bentzel, Grady W.; Naguib, Michael; Lane, Nina J.; Vogel, Sven C.; Presser, Volker; Dubois, Sylvain; Lu, Jun; Hultman, Lars; Barsoum, Michel W.; Caspi, El'ad N.
Abstract : Herein, we report—for the first time—on the additive‐free bulk synthesis of Ti3 SnC2 . A detailed experimental study of the structure of the latter together with a secondary phase, Ti2 SnC, is presented through the use of X‐ray diffraction (XRD), and high‐resolution transmission microscopy (HRTEM). A previous sample of Ti3 SnC2, made using Fe as an additive and Ti2 SnC as a secondary phase, was studied by high‐temperature neutron diffraction (HTND) and XRD. The room‐temperature crystallographic parameters of the two MAX phases in the two samples are quite similar. Based on Rietveld analysis of the HTND data, the average linear thermal expansion coefficients of Ti3 SnC2 in the a and c directions were found to be 8.5 (2)·10 −6 K −1 and 8.9 (1)·10 −6 K −1, respectively. The respective values for the Ti2 SnC phase are 10.1 (3)·10 −6 K −1 and 10.8 (6)·10 −6 K −1 . Unlike other MAX phases, the atomic displacement parameters of the Sn atoms in Ti3 SnC2 are comparable to those of the Ti and C atoms. When the predictions of the atomic displacement parameters obtained from density functional theory are compared to the experimental results, good quantitative agreement is found for the Sn atoms. In the case of the Ti and C atoms, the agreement is more qualitative. We also used first principles to calculate the elastic properties of both Ti2 SnC and Ti3 SnC2 and their Raman active modes. The latter are compared to experiment and the agreement was found to be good.